2003
DOI: 10.1152/japplphysiol.00736.2002
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow and muscle fatigue in SCI individuals during electrical stimulation

Abstract: Our purpose was to measure blood flow and muscle fatigue in chronic, complete, spinal cord-injured (SCI) and able-bodied (AB) individuals during electrical stimulation. Electrical stimulation of the quadriceps muscles was used to elicit similar activated muscle mass. Blood flow was measured in the femoral artery by Doppler ultrasound. Muscle fatigue was significantly greater (three- to eightfold, P < or = 0.001) in the SCI vs. the AB individuals. The magnitude of blood flow was not significantly different betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 65 publications
6
47
1
Order By: Relevance
“…11 Increased fatigability may diminish the ability to sustain sufficient exercise intensity long enough to stimulate cardiovascular adaptations. The initial level of muscle fatigue with our stimulation protocol was 37%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Increased fatigability may diminish the ability to sustain sufficient exercise intensity long enough to stimulate cardiovascular adaptations. The initial level of muscle fatigue with our stimulation protocol was 37%.…”
Section: Discussionmentioning
confidence: 99%
“…10 One potential limitation to NMES training for individuals with SCI is excessive muscle fatigue. [11][12][13] In a recent investigation, individuals with SCI were subjected to an electrical stimulation protocol designed to evoke isometric contractions of the quadriceps muscle group. 11 Muscle fatigue in individuals with SCI was three times greater than that found in AB subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One article investigated the influence of single muscle electrical stimulation on arterial dynamics in those with SCI. 56 This study illustrated that electrical stimulation of the quadriceps femoris leads to increased femoral artery blood flow. In addition, these authors showed that femoral blood flow increases with increasing exercise intensity in SCI participants, suggesting a dose-response relationship.…”
Section: Resultsmentioning
confidence: 77%
“…46 Acute exercise techniques Fourteen papers investigated the vascular effects of a single acute exercise bout. Eight articles were prospective control trials 31,41,[51][52][53][54][55][56] and six were pre-post design. 40,[57][58][59][60][61] Papers investigating acute exercise included: passive leg exercise (n ¼ 3), 53,57,60 FES (n ¼ 3), 54,55,59 single muscle electrical stimulation (n ¼ 1), 56 upper body continuous aerobic exercise (arm cycling or wheeling) (n ¼ 5), 31,40,41,52,58 acute combined arm passive leg exercise (n ¼ 1) 61 and stretchinduced contractions (n ¼ 1).…”
Section: Resultsmentioning
confidence: 99%